KOMUNIKASI KELUARGA DALAM POLA ASUH DAN PENCEGAHAN PERILAKU BULLYING - Lusiawati, Ira (UKRI, 2024)
The family is the center of inheritance of good values. In it there is a transfer of knowledge regarding behavior that should be carried out and what should be avoided. The inheritance of these values ​​takes place through communication. Therefore, communication is very crucial in shaping the mental and spiritual development of family members. If communication is good, it will form a social spirit among family members. However, if family communication is not good it will certainly lead to antisocial behavior. One form of antisocial behavior is bullying. This aggressive behavior, which is manifested by attacking and hurting other people mentally and socially, is certainly very contrary to the family's parenting style. Because in a normal family, they will not teach behavior that attacks and harms other people. Based on this explanation, this research aims to determine the role of family communication in preventing bullying behavior. The method used is descriptive qualitative with a type of media content analysis. A qualitative approach is used to reveal the phenomena behind visible events. The results show that family communication plays a very important role in parenting to shape children's mental and spiritual abilities as provisions for social interactions and to avoid bullying behavior. Key words: Values, family, communication, parenting, bullying